PERAN KEGIATAN PEMBIASAAN PAGI DALAM MENUMBUHKAN NILAI-NILAI KARAKTER DI SDN KANGGRAKSAN - Pirmansyah, Drajat; Kurniasih, Nita; Ikrimah, Ikrimah; Prastika, Varenezza; Khodari, Rahmad (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study aims to examine the implementation of morning routines at Kanggraksan State Elementary School in fostering character values among students, as well as to identify the supporting and inhibiting factors in its implementation. The study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results of the study indicate that morning routine activities are conducted regularly and systematically with a variety of activities such as flag ceremonies, morning prayers, literacy, istighosah, infaq, gymnastics, and cleaning activities that effectively instill religious values, discipline, responsibility, independence, nationalism, and social awareness. The success of this program is supported by the active involvement of teachers, school principals, student participation, parental support, and the role of external parties such as PLP students. However, there are challenges such as the lack of discipline among some students and the tardiness of staff, which require strengthening consistency. Overall, morning routines play a strategic role in shaping positive character traits in students, reflecting behavioral changes toward greater discipline, self-confidence, independence, and concern for the surrounding environment. These findings underscore the importance of morning routines as an integral part of character education in elementary schools ABSTRAKPenelitian ini bertujuan untuk mengkaji pelaksanaan kegiatan pembiasaan pagi di SD Negeri Kanggraksan dalam menumbuhkan nilai-nilai karakter peserta didik, serta mengidentifikasi faktor pendukung dan penghambat pelaksanaannya. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa kegiatan pembiasaan pagi berjalan rutin dan terstruktur dengan variasi aktivitas seperti upacara bendera, doa pagi, literasi, istighosah, infaq, senam, dan kegiatan kebersihan yang efektif menanamkan nilai religiusitas, disiplin, tanggung jawab, kemandirian, nasionalisme, dan kepedulian sosial. Keberhasilan program ini didukung oleh keterlibatan aktif guru, kepala sekolah, partisipasi siswa, dukungan orang tua, serta peran pihak eksternal seperti mahasiswa PLP. Namun, terdapat hambatan berupa kurang tertibnya sebagian siswa dan keterlambatan petugas yang memerlukan penguatan konsistensi. Secara keseluruhan, pembiasaan pagi berperan strategis dalam pembentukan karakter positif siswa yang mencerminkan perubahan perilaku menjadi lebih disiplin, percaya diri, mandiri, dan peduli terhadap lingkungan sekitar. Temuan ini menegaskan pentingnya pembiasaan pagi sebagai bagian integral dari pendidikan karakter di sekolah dasar.